Validasi Komik Asertif Organ Reproduksi Seri “Bagian Tubuh”: (Prevensi Kekerasan Seksual pada Anak Usia Dini) - Tri Suyati; Padmi Dhyah Yulianti; Ellya Rakhmawati (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2020)
Abstract: Sexual violence in early childhood is prevalent and shows an increasing prevalence. The impact caused by the occurrence of sexual violence experienced will affect the mental health of the victim. Therefore, early childhood needs to be saved from incidents of sexual violence because children are the future owners of the nation. Thus, the importance of equipping children with knowledge, attitudes and skills about themselves and their bodies to prevent sexual violence. The researchers in this study aim to produce Reproductive Organ Assertive Comics for early childhood and test the validity of assertive comics with the theme